Matematyka

Autorzy:Wojciech Babiański, Lech Chańko, Joanna Czarnowska

Wydawnictwo:Nowa Era

Rok wydania:2015

Przedstaw wyrażenie w postaci kwadratu 4.57 gwiazdek na podstawie 7 opinii
  1. Liceum
  2. 1 Klasa
  3. Matematyka

`a)\ x^2+6x+9=x^2+2*x*3+3^2=(x+3)^2` 

`b)\ 4x^2+4x+1=(2x)^2+2*2x*1+1^2=(2x+1)^2` 

`c)\ x^2-x+1/4=x^2-2*x*1/2+(1/2)^2=(x-1/2)^2` 

`d)\ 4x^2-20x+25=(2x)^2-2*2x*5+5^2=(2x-5)^2` 

`e)\ 16x^2+24x+9=(4x)^2+2*4x*3+3^2=(4x+3)^2` 

`f)\ x^2-3x+9/4=x^2-2*x*3/2+(3/2)^2=(x-3/2)^2`